Code-Oriented Global Design Parameters for Moment-Resisting Steel Frames with Metallic Structural Fuses - Tena-Colunga, Arturo; Hernández-Ramírez, Héctor (Frontiers in Built Environment, 2017)
In this paper the authors summarize the results of a parametric study devoted to evaluate the seismic behavior of low to medium rise regular special moment-resisting steel frames (SMRSFs) with hysteretic energy dissipation devices mounted on chevron steel bracing. For that purpose, 270 different building models were designed considering typical story heights and bay widths used in Mexican practice. The parameters under study were: (1) number of stories: 5, 10, 15, 20 and 25, (2) elastic stiffness ratios () between the moment frame system and the whole structure (frame-bracing-hysteretic device system): =0.25, 0.50 and 0.75, (3) different elastic stiffness balances () between the hysteretic device and the supporting braces: =0.25, 0.50 and 0.75, (4) post to pre yielding stiffness ratios (K2/KELD) for the hysteretic devices of 0.0 (elastic-perfectly plastic), 0.03 and 0.05 and, (5) two angles of inclination of the chevron braces with respect to the horizontal axis (): 400 and 450. From the results obtained in this study, optimal stiffness balances  and  are defined to obtain a suitable mechanism where the hysteretic devices yield first and develop their maximum local displacement ductility , whereas incipient yielding is only formed at beam ends of the moment frame. Observations are done with respect to: (a) the global ductility capacity for the structure and its relationships with the local displacement ductility capacity for the hysteretic devices for a given combination of , , K2/KELD and , and (b) overstrength factors () for design purposes.